Consistent time discretization for a dynamical frictional contact problem and complementarity techniques - Vola, Didier; Pratt, Elaine; Jean, Michel; Raous, Michel (European Journal of Computational Mechanics, 1998)
The dynamical problem of a viscoelastic body in volving unilateral contact and Coulomb friction is set so as to take into account accurately eventual discontinuities of the relative velocities when impacts occur. Several first order implicit numerical schemes for the time discretized equations of the problem are proposed. The results are compared to those of a higher order standard numerical scheme. The dicrete problem, with the velocity as unknown, set in terms of a complementarity problem which is solved by Lemke's mathematical programming method.